International trade theory in a developing world : proceedings of a conference held by the International Economic Association - Harrod, Roy (ed.); Hague, D. C (ed.); International Economic Association (London : Macmillan, 1963)
This book explore the problems associated with international trade and investment in relation to economic policy making.
includes appendixes
ijb, 16/01/2019
Loans